Uji Organoleptik (Sensori) dan Kadar Air Pembuatan Cookies dengan Penambahan Tepung Biji Nangka (Artocaprus heteroypllus) - Selvianti, Isye; Dwi Hastuti, Ningrum; Indriawan, Rois (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
Cookies are cakes made from flour which are generally made from wheat flour, powdered sugar, chicken eggs, vanilla, margarine, cornstarch, baking powder and instant milk powder, but often along with the increasing need for wheat flour it has an impact on the level of consumption of wheat. in Indonesia is not sufficient. Efforts are being made to minimize the use of wheat flour by means of substitution, one of which is by substituting jackfruit seed flour. The purpose of this research is to determine the level of preference for cookies with the addition of jackfruit seed flour and water content using various methods (p0= 100g : 0g), (P1= 100g: 40g), (P2= 100g : 50g) and (P3= 100g: 60g). The results obtained using the organoleptic test for color, aroma, taste and texture. In color, the best value was found in treatment P2, namely 7.32%, aroma was found in treatment P3, namely 7.24%, taste was found in treatment P1, namely 7.96%, and on the texture the highest value was found in treatment P2, namely 7.68%. In the water content test, the highest value was found in treatments P1 and P2, namely 16%.